Rho is Required for the Initiation of Calcium Signaling and Phagocytosis by Fcγ Receptors in Macrophages - Hackam, David J. (The Rockefeller University Press, 1997)
Phagocytosis of bacteria by macrophages and neutrophils is an essential component of host defense against infection. The mechanism whereby the interaction of opsonized particles with Fcγ receptors triggers the engulfment of opsonized particles remains incompletely understood, although activation of tyrosine kinases has been recognized as an early step. Recent studies in other systems have demonstrated that tyrosine kinases can in turn signal the activation of small GTPases of the ras superfamily. We therefore investigated the possible role of Rho in Fc receptor–mediated phagocytosis. To this end we microinjected J774 macrophages with C3 exotoxin from Clostridium botulinum, which ADP-ribosylates and inactivates Rho. C3 exotoxin induced the retraction of filopodia, the disappearance of focal complexes, and a global decrease in the F-actin content of J774 cells. In addition, these cells exhibited increased spreading and the formation of vacuolar structures. Importantly, inactivation of Rho resulted in the complete abrogation of phagocytosis. Inhibition of Fcγ receptor–mediated phagocytosis by C3 exotoxin was confirmed in COS cells, which become phagocytic upon transfection of the FcγRIIA receptor. Rho was found to be essential for the accumulation of phosphotyrosine and of F-actin around phagocytic cups and for Fcγ receptor–mediated Ca(2+) signaling. The clustering of receptors in response to opsonin, an essential step in Fcγ-induced signaling, was the earliest event shown to be inhibited by C3 exotoxin. The effect of the toxin was specific, since clustering and internalization of transferrin receptors were unaffected by microinjection of C3. These data identify a role for small GTPases in Fcγ receptor–mediated phagocytosis by leukocytes.